Financial Performance Evaluation in Property Companies Using the Residual Income Method - Vina Winda Sari (IHSA Institute, 2025)
This research aimed to evaluate the financial performance of property companies using the Residual Income (RI) method. The central research problem was to identify a more effective and accurate way of assessing the value creation and financial health of property companies, given the complexities of capital investment in the real estate sector. The objective was to determine how the RI method, which incorporates the cost of equity into performance evaluation, can provide more insightful results compared to traditional methods. The applied research method involved using the Residual Income model to assess the financial performance of selected property companies. Data from financial statements, including net income and equity costs, were analyzed step by step to calculate RI for each company. The study found that the RI method offers a more reliable indication of whether a company is generating returns that exceed its cost of capital, providing valuable insights into long-term profitability and shareholder value. The results highlighted that property companies with positive residual income are more likely to be creating value for shareholders, while those with negative residual income may need to reassess their capital allocation strategies. The RI method was found to be particularly useful for investors and financial analysts in making more informed decisions about company valuations and investment opportunities in the property sector.